Análise comparativa do tratamento do ardor bucal com terapia a laser de baixa intensidade e estimulação elétrica nervosa transcutânea: um ensaio clínico randomizado - Medeiros, Cristianne Kalinne Santos (2022)
Introduction: The management of patients with burning mouth is a challenge in the clinical routine of dentistry. Objective: To compare the effect of Low Intensity Laser Therapy (LLLT) and Transcutaneous Electrical Nerve Stimulation (TENS) in the treatment of burning mouth. Methodology: Randomized clinical trial consisting of 25 patients with burning mouth who were treated with TENS (n=12) and LLLT (n=13). Treatment protocols were applied weekly for 8 weeks. The two-way analysis of variance (ANOVA) test was used to verify whether there was a significant difference between the times T0 (before starting treatment), T1 (after the 4th treatment session), T2 (after the 8th treatment session) and T3 (30 days after the end of treatment) in relation to symptoms, analyzed using the Visual Analogue Scale (VAS), unstimulated salivary flow, xerostomia and dysgeusia with TENS and LLLT interventions. Results: Most patients were female in the postmenopausal period, with a mean age of 59.25 years in the TENS group and 62.08 in the LLLT group. Hypertension and dyslipidemia were the most frequent systemic alterations. Anxiety and depression were the only psychiatric disorders reported. Most patients used drugs such as antihypertensives and antidepressants. Significant variations were not observed with regard to xerostomia and dysgeusia in the two groups analyzed. TENS and LLLT were effective in reducing the symptoms reported by patients (p˂0.001), however, it was observed between times T2 and T3 that the LLLT group showed a better response when compared to TENS (p=0.003). Patients in the TENS group showed an increase in salivary flow between times T1 and T2, while the LLLT group showed a decrease (p=0.052). Conclusion: TENS and LLLT were effective in reducing the symptoms of burning mouth during treatment and 30 days after the end of treatment, and the LLLT group showed a better response in the posttreatment follow-up session when compared to the TENS group.